Extraction and characterization of pectin from the fruit peel of Benincasa hispida (Thunb.) cogn - La Ode Akbar Rasydy; Nita Rusdiana; Mira Eria Anggarini (Universitas Ahmad Dahlan, 2022)
Pectin is a polysaccharide and a major component of most plant cell walls and serves as an adsorbent, emulsifying agent, gelling agent, stabilizer, and gelling agent. Pectic can be obtained from the fruit peel of Bligo (Benincasa hispida (Thunb.) Cogn). This study aims to determine the presence of pectin in the peel of Bligo fruit, which can be used as a gelling agent, and to obtain the best solvent concentration and time for the extraction and characterization of pectin from the peel of Bligo fruit by using a completely randomized design (CRD) using 4 variations. Concentration of citric acid solvent (5%,7%,9% and 11%) with extraction time consisting of 4 levels (30, 60, 90 and 120 minutes). The characteristics of the pectin produced were determined based on its water and ash content, equivalent weight, methoxyl content, galacturonic acid content, and degree of esterification. The results showed that the highest yield was obtained from 7% citric acid concentration with an extraction time of 60 minutes, with the value of 9.8%. The resulted pectin had a water content of 10.4%; ash content of 8.75%; an equivalent weight of 779.243 mg; methoxyl content of 2.515%; galacturonic acid content of 114.685%; and esterification degree of 12.445%. The characterization of functional groups using FTIR showed groups -OH, -CH3, -C=O, -C-H, and -R-OR with wavelength respectively of 2958.93 cm-1; 1396.52 cm-1; 1724.36 cm-1; 1416.78 cm-1; and 1220.99 cm-1.